Estudios y diseños de la presa de embalse del parque del conocimiento ESPOL - Carrión Rodríguez, Rodrigo (2009)
The following work has as main objective design and study the Park of the Knowledge project’s damn. The construction of reservoir involves 20ha approximately from Gustavo Galindo Velasco’s Campus, getting with it a beautiful lake, which principal function is to provide landscaping. The designed Damn, has the next characteristics: is a soil damn, zoned type, with weak rock slopes, waterproof clay kernel, filters-drains and rock protection, when being built it will have 22 of height and it is constituted in the closing of two gulches that they skirt the facilities of the Park of the knowledge that are already being built; it also has an spillway which will be construct in the left side from the vase. With a capacity of 1250000 m3, this reservoir will be the largest inside Gustavo Galindo Velasco Polytechnic Campus, too.